Impact of the Olig Family on Neurodevelopmental Disorders - Szu, Jenny; Wojcinski, Alexandre; Jiang, Peng; Kesari, Santosh (Frontiers in Neuroscience, 2021)
The Olig genes encode members of the basic helix-loop-helix (bHLH) family of transcription factors. Olig1, Olig2, and Olig3 are expressed in both the developing and mature central nervous system (CNS) and strictly regulate cellular specification and differentiation. Extensive studies have established functional roles of Olig1 and Olig2 in directing neuronal and glial formation during different stages in development. Recently, Olig2 overexpression was implicated in neurodevelopmental disorders Down syndrome (DS) and Autism Spectrum Disorder (ASD) but its influence on cognitive and intellectual defects remains unknown. In this review, we summarize the biological functions of the Olig family and how it uniquely promotes cellular diversity in the CNS. This is followed up with a discussion on how abnormal Olig2 expression impacts brain development and function in DS and ASD. Collectively, the studies described here emphasize vital features of the Olig members and their distinctive potential roles in neurodevelopmental disease states.